2018
DOI: 10.1001/jamaoncol.2018.1684
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Diabetes After Cancer Development

Abstract: In this large Korean cohort, cancer development increased the risk of subsequent diabetes. These data provide evidence that cancer is associated with an increased risk of diabetes in cancer survivors independent of traditional diabetes risk factors. Physicians should remember that patients with cancer develop other clinical problems, such as diabetes, with higher frequency than individuals without cancer, and should consider routine diabetes screening in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 60 publications
0
137
0
Order By: Relevance
“…The highest risk of diabetes within the first year may be associated with medical surveillance before and after cancer treatment. Hwang et al [19] also reported that the strongest risk of diabetes was among cancer patients in the first 2 years after cancer diagnosis, but the association was not significant (HR ¼ 1.17, 95%CI ¼ 0.77, 1.76) among endometrial cancer survivors. However, our study supports the hypothesis that endometrial cancer diagnosis is associated with a higher risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The highest risk of diabetes within the first year may be associated with medical surveillance before and after cancer treatment. Hwang et al [19] also reported that the strongest risk of diabetes was among cancer patients in the first 2 years after cancer diagnosis, but the association was not significant (HR ¼ 1.17, 95%CI ¼ 0.77, 1.76) among endometrial cancer survivors. However, our study supports the hypothesis that endometrial cancer diagnosis is associated with a higher risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…While previous studies suggest an increased risk of endometrial cancer with previous history of diabetes [13e18], limited evidence has been established that the risk for diabetes is increased after diagnosis of endometrial cancer. A recent study in Korea reported no association between endometrial cancer and subsequent diabetes, but the risk of diabetes by diabetes types and risk factors for diabetes were not investigated [19]. Further, there is no previous study, to our knowledge, that examined whether the risk of diabetes after endometrial cancer diagnosis differs in comparison with a general population.…”
Section: Introductionmentioning
confidence: 92%
“…Finally, data on clinical outcomes were based on claims data and there might be misclassification of COPD or lung cancer. However, the NHIS routinely audits the claims6 and the data for cancer outcomes are considered highly reliable and have been used in numerous peer-reviewed publications 8 9…”
Section: Discussionmentioning
confidence: 99%
“…NHIS claims for inpatient visits, outpatient visits, procedures and prescriptions were coded using the International Classification of Diseases, 10th Revision and the Korean Drug and Anatomical Therapeutic Chemical Codes 7. Lung cancer was defined as the presence of the same C33 or C34 code more than three times within a year or an inpatient hospitalisation with a C33 or C34 code 8. COPD was defined as the presence of J43-J44 (except J43.0) codes and use of COPD medications at least twice within a year 9.…”
Section: Methodsmentioning
confidence: 99%
“…Type 2 diabetes was defined as either ≥2 visits for which type 2 diabetes-related diagnostic codes (E11 [Type 2 diabetes], E12 [Malnutrition-related diabetes mellitus], E13 [Other specified diabetes mellitus], and E14 [Unspecified diabetes mellitus]) were assigned between 2002 and 2013 or 1 visit with a type 2 diabetes diagnosis and a filled prescription for diabetes-related medications, including metformin, nateglinide, repaglinide, insulin, sitagliptin, saxagliptin, linagliptin, alogliptin, acarbose, glimepiride, glibenclamide, gliclazide, glipizide, rosiglitazone, pioglitazone, dapagliflozin, ertugliflozin, liraglutide, exenatide, and dulaglutide. This definition of type 2 diabetes was adopted from Yul et al51 .…”
mentioning
confidence: 99%